2008
DOI: 10.1111/j.1365-313x.2008.03401.x
|View full text |Cite
|
Sign up to set email alerts
|

LZF1, a HY5‐regulated transcriptional factor, functions in Arabidopsis de‐etiolation

Abstract: SummaryWe surveyed differential gene expression patterns during early photomorphogenesis in both wild-type and mutant Arabidopsis defective in HY5, an influential positive regulator of the responses of gene expression to a light stimulus, to identify light-responsive genes whose expression was HY5 dependent. These geneexpression data identified light-regulated zinc finger protein 1 (LZF1), a gene encoding a previously uncharacterized C2C2-CO B-box transcriptional regulator. HY5 has positive trans-activating ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
199
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(209 citation statements)
references
References 82 publications
8
199
1
1
Order By: Relevance
“…Previous studies have shown that several B-box proteins, including STH2 and LZF1 (STH3), which both directly interact with HY5, play roles in light signaling (Datta et al, 2007(Datta et al, , 2008Chang et al, 2008;Kumagai et al, 2008). Despite extensive efforts, we did not detect any direct interaction between BBX32 and HY5, nor did we find an interaction of BBX32 with DNA.…”
Section: Bbx32 Functions In a Regulatory Protein Complex To Modulate contrasting
confidence: 53%
See 4 more Smart Citations
“…Previous studies have shown that several B-box proteins, including STH2 and LZF1 (STH3), which both directly interact with HY5, play roles in light signaling (Datta et al, 2007(Datta et al, , 2008Chang et al, 2008;Kumagai et al, 2008). Despite extensive efforts, we did not detect any direct interaction between BBX32 and HY5, nor did we find an interaction of BBX32 with DNA.…”
Section: Bbx32 Functions In a Regulatory Protein Complex To Modulate contrasting
confidence: 53%
“…HY5 is known to interact with other B-box proteins like STH2/BBX21 and LZF1/STH3/BBX22, which function positively in light signaling with HY5; null mutations in STH2/BBX21 and LZF1/STH3/BBX22 genes cause phenotypes similar to the hy5 mutants (Datta et al, 2007(Datta et al, , 2008Chang et al, 2008). BBX32 might either directly interact with HY5 and/or bind one or more of the other B-box proteins that interact with HY5.…”
Section: Bbx32 Interacts With Sth2mentioning
confidence: 99%
See 3 more Smart Citations